ANALISIS CEMARAN LOGAM TIMBAL (PB) DALAM SEDIAAN KOSMETIK EYELINER PENSIL DAN LIPSTIK BERBAGAI MERK YANG BEREDAR DI MARKETPLACE MENGGUNAKAN SPEKTROFOTOMETER SERAPAN ATOM (SSA) - Aisha, Audyra Zahra; Dewi, Cinta Amalia Kurnia; Cahyadi, Doni Nur; Nugraheni, Estiningtyas; Amaris, Eugenia; Maharani, Laila; Maisyaroh, Ratih; Faizah, Riris Fityatun Nur; Hariyani, Hariyani (Jurnal Riset Kefarmasian Indonesia, 2025)
Cosmetic preparations come into direct contact with the outside of the body (skin), so the product must be safe from various contaminants. In cosmetic preparations, heavy metal lead is intentionally added to give the impression of a shiny and bright colour; in addition, lead contamination contained in cosmetic products can come from raw materials or equipment in the production process. This study aims to analyze the content of heavy metal lead (Pb) in cosmetic preparations of eyeliner pencil and lipstick from various brands, validate the analysis method, and evaluate the assessment of the maximum limit of heavy metal lead in cosmetic preparations based on the Regulation of the Head of the Food and Drug Supervisory Agency of the Republic of Indonesia Number 16 of 2024 concerning Contamination Limits in Cosmetics. The analysis method used is the Atomic Absorption Spectrophotometer (AAS) instrument. Sample preparation was carried out using the wet destruction method, the procedure was carried out by mixing concentrated HNO₃ and HCl in a ratio of 1:3. The results of the analysis using the Atomic Absorption Spectrophotometer (AAS) instrument showed that the highest lead content in the eyeliner pencil sample was 7.8823 ± 0.4075 mg/Kg; and in the lipstick sample was 118.5490 ± 0.6479 mg/Kg. Based on the results of the study, it can be concluded that the three cosmetic products of eyeliner pencil of various brands have met the requirements of BPOM RI No. 16 of 2024, while of the three samples of lipstick cosmetic preparations, there was one sample that did not meet the requirements for lead content in cosmetic preparations based on BPOM RI No. 16 of 2024.